Combining quantitative genetics and genomics to identify polymorphisms associated with drought physiology in Arabidopsis and Brassica napus - Fletcher, Richard, author; McKay, John, advisor; Bauerle, William, committee member; Byrne, Patrick, committee member; Leach, Jan, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.